Here [videorecording (DVD)] - King, Braden; Foster, Ben, 1980-; Azabal, Lubna; Coyote, Peter (Strand Releasing Home Video, 2012)
Set against the landscape of Armenia, chronicles a brief but intense relationship between an American satellite-mapping engineer and an expatriate photographer who impulsively decide to travel across the remote countryside.